RELEVANCE OF TOOLS FOR ASSESSING THE READINESS OF THE HEALTH CARE SYSTEM TO FUNCTIONING IN CONDITIONS OF MILITARY THREAT - Bilas, Markiian (Public Management and Policy, 2025)
The relevance of the topic is driven by the need to strengthen the resilience and alertness of the healthcare system, as well as to ensure comprehensive and regular monitoring of its response capacity. The purpose of the article is to examine the alignment of existing health emergency preparedness assessment tools with the challenges that proved most critical for Ukraine’s healthcare system during full-scale warfare. A step-by-step methodology was applied. The first stage involved analyzing the content of current tools for assessing healthcare systems’ emergency preparedness. The second stage included a content analysis of 11 representative sources (2022–2024), including reports by WHO, the Ministry of Health of Ukraine, and the National Health Service of Ukraine, on the functioning of Ukraine’s healthcare system under wartime conditions. The Health Emergency and Disaster Risk Management Framework (Health EDRM) was used for synthesis. In the third stage, a comparative analysis was conducted to identify the presence of critical response components—derived from Ukraine’s experience—in each of the tools. The article presents the results of this analysis, highlighting the relevance of the tools to Ukraine’s wartime context. Five key assessment tools were systematized. Based on empirical data structured via the Health EDRM model, six critical response components were identified. The tools that best covered the priority components necessary for healthcare system functionality during full-scale war were determined. The study emphasizes the importance of further research aimed at developing and implementing national indicators and tools for evaluating preparedness for health emergencies. The need for continued development, adaptation, and implementation of such tools and indicators at the national level is substantiated.